PENGAJARAN AGAMA KATOLIK DI SEKOLAH MENUMBUHKAN NILAI KEJUJURAN DAN KEBENARAN DALAM DIRI PESERTA DIDIK - Wahyuni, Sri; Wilhelmus, Ola Rongan (CREDENDUM: Jurnal Pendidikan Agama, 2024)
Honesty and truth are the important values ​​for human life because they are related to the good behaviors. Educational institution has an important role in educating students’ character of being honesty and truth in the life of students at school. Catholic religious teaching in schools is an effort made by a Catholic religious teacher to instill so called Christian values of honesty and truth in life of students. The research conducted with the following aims: 1) to analyze the extent of efforts made by Catholic religious teacher to instill the values ​​of honesty and truth in students’ life; and 2) to analyze the extent to which those values taught by Catholic religious teachers have a positive impact on the students' behavior. The research was conducted using qualitative methods. Research data was obtained through individual interviews. Research data analysis used an inductive approach. The results of research data analysis revealed that majority of informants revealed that they had tried their best to instill the values ​​of honesty and truth in the life of students through Catholic religious teaching in schools.